Seed quality of sorghum (Sorghum bicolor L. Moench) isocytoplasmic genotypes. - Pecina, Víctor (2016)
The production of sorghum hybrids depends almost entirely on one genic-cytoplasmic sterility system (Milo-Kafir, A1 Cytoplasm), therefore its importance in increasing the diversity of the number of male-sterile sources, as the named A2 Cytoplasm. This system was introduced at the Rio Bravo Experiment Station (lNIFAP-CIRNE) in Tamaulipas, Mexico, where ge-netic material and seed production were developed. The objetive was to compare the seed quality ofthe isocytoplasmic genotypes (A1 and A2 cytoplasm). A Completely Radomized Experimental Design with Factorial Arrangement and two replications was used. The results show that there were no differences between the two types of cytoplasm (A1 and A2) for the following quality traits: volumetric weight of seeds, 1000 seeds' weight, germination(G) and seedling dry weight (SDW), through nine months of storage; whereas in vigor (G and SDW after fast aging) the A2 cytoplasm surpassed the Al cytoplasm and the same behavior was observed on the seed harvested at its physiological maturity, while at harvest maturity the Al was superior in G and SDW.